Prevent Stunting through Socialization of the Importance of Immunization to Achieve Universal Child Immunization (UCI) - Louisa Ariantje Langi; Genoveva Adjeng Dwynaratu; Anastasia Novena Brigita Weubun; Raynald Mitra Hadi Palamba; Jumaini Andriana Sihombing; Maria Carmelia Celly Mau (International Journal Of Community Service, 2025)
Immunization program is an important step to provide protection against certain diseases, especially for groups that are vulnerable to infection, such as infants, toddlers, children, women of childbearing age, and pregnant women. Through this program, Indonesia has successfully gained recognition as free from smallpox by WHO since 1974. In Indonesia, every infant (aged 0-11 months) is required to receive complete basic immunization, which includes 1 dose of Hepatitis B, 1 dose of BCG, 3 doses of DPT-HB-Hib, 4 doses of polio, and 1 dose of measles. One indicator of the success of this immunization program is the achievement of Universal Child Immunization (UCI), which is a condition where all infants (under one year of age) receive complete basic immunization. However, data shows that parental awareness of the importance of immunization is still low, so that many children end up not getting immunized. For this reason, it is necessary to carry out activities in an effort to provide awareness and understanding of the importance of immunization through socialization activities. The socialization activity was carried out in Pamekaran Village, Rancakalong District, Sumedang Regency, West Java with 34 participants consisting of mothers of toddlers. The method used was socialization accompanied by measuring initial knowledge (pre-test) and post-test) about the importance of immunization.The results of the activity had an impact, namely there was an increase in knowledge of participants with a good category about the importance of immunization, namely from 12 people or 35.2 percent (pre-test) to 27 out of 34 participants or 79.4 percent. In other words, there was an increase in the number of participants with good knowledge by 44.2 percent. Conclusion: the socialization activity had a positive impact and resulted in an increase in knowledge of Pamekaran Village residents about the importance of immunization